ПЕДАГОГИКАЛЫҚ ТЕХНОЛОГИЯЛАРДЫ ДУРЫС ТҮСИНИЎ ҲӘМ ҚОЛЛАНЫЎ ХАҚҚЫНДА - Урумбаева, А.Н. (FAN va JAMIYAT, 2018)
The article is devoted to the analytical review about correct understanding and use of pedagogical technologies in the educational process. The author gives information about the types of pedagogical technologies and levels of their usage.